The Lion King 1 1/2 [videorecording (DVD)] - Raymond, Bradley; Guillaume, Robert; Sabella, Ernie; Broderick, Matthew, 1962-; Lane, Nathan, 1956-; Harper, Don; Goldberg, Whoopi, 1955-; Kavner, Julie; Stiller, Jerry; Kelly, Moira; Marin, Cheech; Zimmer, Hans (Walt Disney Studios Home Entertainment : Distributed by Buena Vista Home Entertainment, 2011)
See the real story behind the lion king--at least from Timon and Pumbaa's perspective. The truth will be exposed about some "passed" events - such as when King Mufasa introduced his young heir to the animal kingdom. Reveals the true hullabaloo behind their departures from the meerkat and warthog 'hoods. Tag along as the two buddies from the brush search for their dream home, share their joys and trials as they raise young Simba using the "Hakuna Matata" philosophy, then cheer them as they help Simba save the Serengeti and reclaim his place atop Pride Rock.